Gender stereotypes in Tuvan proverbs and sayings - Egorova, Aida I.; Kondakova, Agrafena P.; Kuzhuget, Maria A. (The New Research of Tuva, 2020)
The article examines traditional gender stereotypes as they appear in Tuvan paroemias and the assessment of these paroemias by Tuvan respondents. The survey made use of the method of intent analysis to identify the intentions (hidden agendas) of proverbs and sayings, and also of the scale of assessment of gender stereotypes. For our study, we selected 75 proverbs and sayings containing a description of male and female behavior. To evaluate and compile the scale, the list was narrowed down to 45 paroemias reflecting gender stereotypes and social behavior of men and women. In June 2018, 120 Tuvans of both genders were surveyed, belonging to either of the two age groups - 18 to 35 and 36 and abover.On the whole, Tuvan paremias reflect in detail the hidden intentions of gender stereotypes. The paremias present traditional family and tribal relations based on patriarchal attitudes, regulation of gender differences and dichotomization of male and female. Male stereotypes, as reflected in Tuvan proverbs, feature such hidden intentions as «Praise», «Evaluation», «Instruction», «Advice», «Teaching», while female Tuvan stereotypes focus on intentions like «Instruction», «Evaluation», «Praise», «Teaching», «Condemnation».Respondents largely agree with the traditional views of male and female behavior and tend to be sexist to women. These trends are especially pronounced in men and in older people. There was no significant difference between the sex and age samples in the assessment of proverbs.
Keywords: Tuvan language; paroemia; proverbs; sayings gender stereotypes; male stereotypes; female stereotypes; androcentrism; androcracy